Ultrastructural and biochemical analysis of epidermal xanthophores and dermal chromatophores of the teleost Sparus aurata - Ferrer, C.; Solano, F.; Zuasti, A. (Murcia : F. Hernández, 1999)
We have studied the pigmentary system of the teleost Sparus aurata skin by electron microscopy and chromatographic analysis. Under electron microscopy, we found the dermis to contain the three major types of recognized chromatophores: melanophores, xanthophores and iridophores. Melanophores were more abundant in the dorsal region, whereas the iridophores were more abundant in the ventral region. The most important discovery was that of epidermal xanthophores. Epidermal xanthophores were the only chromatophores in the epidermis, something only found in S. azirara and in a teleost species living in the Antartic sea. In contrast, the biochemical analysis did not establish any special characteristics: we found pteridine and flavin pigments located mostly in the pigmented dorsal region. Riboflavin and pterin were two of the most abundant coloured pigment types, but other colourless pigments such as xanthopterin and isoxanthopterin were also detected.